Postinfective Glomerulonephritis (PIGN) in Children Attending a Tertiary Care Centre in Nepal - Poudel, DR; Basnet, S; Gami, FC (Journal of Nepal Paediatric Society, 2015)
Introduction: Post infectious glomerulonephritis (PIGN) is one of the common paediatric kidney disease in developing countries. This study was undertaken to describe the common clinical features, biochemical findings and complications in children with PIGN. Materials and Methods: This was a retrospective descriptive study in which 30 patients admitted with a diagnosis of PIGN at Tribhuvan University Teaching Hospital (TUTH) in a six month period (July 2014 to Dec 2014) were included. Hospital medical records were reviewed for the data collection. Results: Out of 30 patients, 24 (80%) were between 5 to 15 years of age (mean age of 11.5±3.3) with male to female ratio of 2.3:1. Pedal oedema and hypertension were the clinical features seen in 29 (97%) and 28 (93%) patients respectively. Hypocomplementemia was found in 29 (97%) patients. Recent past history of sore throat seen in 10 (33%) patients and skin lesions in 12 (40%). The complications noted were congestive cardiac failure in 5 (17%) patients, rapidly proliferative glomerulonephritis in 3 (10%) and encephalopathy in 1(3%). Conclusion: The most important clinical and biochemical profile observed in nepalese children with PIGN are the hypertension, pedal edema and hypocomplementemia. J Nepal Paediatr Soc 2014;34(3):221-224 DOI: http://dx.doi.org/10.3126/jnps.v34i3.10707